Proses Identifikasi Risiko Inspection Container di PT Tanto Intim Line Cabang Jakarta Utara - Noviana Puspitasari; Edgar Nicholas Saputra (Port Management and Maritime Administration Journal, 2025)
This research aims to determine the risk identification process for container inspection at PT Tanto Inti Line, North Jakarta branch. This research uses a qualitative approach using descriptive methods and interviews. Data was obtained by direct observation and interviews. Control and Resolution Research Results that will not harm the company in an optimal way. PT. Tanto Intim Line North Jakarta Branch continues to improve service performance for consumers or service users in order to achieve loading and unloading of vehicles and passengers. Research Conclusion: The Risk Identification Process of Container Inspection at PT Tanto Intim Line North Jakarta Branch is running according to the procedures that have been carried out.